POLITICS AND AI: COMMUNICATION STYLE OF PRESIDENTIAL CANDIDATE PRABOWO-GIBRAN'S POLITICAL CAMPAIGN - Muhammad Luthfi Maulana; Budi Harjono (Universitas Katolik Soegijapranata, 2024)
The communication model carried out by Prabowo-Gibran in the 2024 presidential election contestation campaign is mass communication. The purpose of this research is to deepen the impact of AI technology in political contestation that occurs in Indonesia. The theory used is Hypodermic Needle Communication using a mechanistic paradigm approach. This research uses a qualitative method with a descriptive approach. The descriptive approach was chosen in order to comprehensively understand the phenomenon that is happening. This research aims to help understand the impact of AI technology in a political context. In this case, the effectiveness of Prabowo-Gibran presidential candidates' political communication in the 2024 political campaign is the main subject for this research. This research adopts a qualitative method with a focus on a descriptive approach. The selection of the descriptive approach aims to thoroughly in-depth the existing phenomenon. The main focus of the research is to evaluate the effectiveness of political communication from presidential candidate Prabowo-Gibran in the 2024 political campaign. The use of AI in visual design communication aims to create a campaign that prioritizes navigation that gives the impression of fun but still provides useful knowledge and information. Given that the focus of the mechanistic paradigm and the Hypodermic Needle communication theory is the impact of communication, the use of AI in illustration and visualization increases the effectiveness of communication in the Prabowo-Gibran campaign more massively.